2013
DOI: 10.1111/cobi.12122
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of Genetic Structure to Assess Population Dynamics of Reintroduced Swift Foxes

Abstract: Reintroductions are increasingly used to reestablish species, but a paucity of long-term postrelease monitoring has limited understanding of whether and when viable populations subsequently persist. We conducted temporal genetic analyses of reintroduced populations of swift foxes (Vulpes velox) in Canada (Alberta and Saskatchewan) and the United States (Montana). We used samples collected 4 years apart, 17 years from the initiation of the reintroduction, and 3 years after the conclusion of releases. To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 91 publications
1
22
0
Order By: Relevance
“…The uncorrelated allele model was chosen as there is evidence that the correlated model may overestimate the number of populations (Guillot et al . ; Cullingham & Moehrenschlager ). The uncertainty of the coordinates was set to zero assuming that individuals have the same geographical provenance within each sampling region.…”
Section: Methodsmentioning
confidence: 99%
“…The uncorrelated allele model was chosen as there is evidence that the correlated model may overestimate the number of populations (Guillot et al . ; Cullingham & Moehrenschlager ). The uncertainty of the coordinates was set to zero assuming that individuals have the same geographical provenance within each sampling region.…”
Section: Methodsmentioning
confidence: 99%
“…Noninvasive genetic sampling provides critical insight into the viability and recovery of populations of rare or cryptic species (Waits and Paetkau 2005, Smith et al 2009, Cullingham and Moehrenschlager 2013, Woodruff et al 2016, DeMay et al 2017). In this study, we showed the value of noninvasive genetic sampling to monitor a population of a threatened habitat specialist, the New England cottontail, through 5 years of reintroduction efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Successful reintroductions must overcome obstacles such as unstable demographics (Murrow et al 2009), skewed sex ratios (Tella 2001, Clout et al 2002), disease (Viggers et al 1993), inbreeding depression (Brook et al 2002, O'Grady et al 2006), stochastic events related to weather or predation (Stacey and Taper 1992), and limited habitat or population connectivity in metapopulation systems (Chandler et al 2015). Genetic monitoring is a valuable tool to evaluate the success of reintroductions and facilitate decision‐making in an adaptive management context (Schwartz et al 2007, De Barba et al 2010, Cullingham and Moehrenschlager 2013, DeMay et al 2017). Specifically, noninvasive genetic sampling of DNA extracted from hair, feathers, feces, or other shed tissues can be used to monitor populations.…”
mentioning
confidence: 99%
“…This finding has prompted a closer investigation of previously collected genetic data, where a small number of microsatellites were used to assess the genetic status of the reintroduced population. These data indicated a stable, mid‐range level of genetic diversity, and evidence of increasing effective population size (Cullingham & Moehrenschlager, ). However, there was evidence of population substructure, with two subpopulations being identified: “east” and “west”, Fig.…”
Section: Introductionmentioning
confidence: 92%
“…We used hair samples collected in 2000/01 (N = 111) and 2005/06 (N = 193) that were previously analysed at seven microsatellite loci (Cullingham & Moehrenschlager, 2013). To determine parentage among these samples, we genotyped an additional 11 microsatellite loci and a sex-determining locus (ZFX/ZFY; Morin et al, 2005).…”
Section: Sample Collection and Genotypingmentioning
confidence: 99%